2023
DOI: 10.3390/ijerph20043670
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Functioning Profile of Adolescents with Anorexia before and during the COVID-19 Pandemic: A Cross-Sectional Study on Mentalizing, Alexithymia, and Impulsiveness

Abstract: Anorexia nervosa (AN) usually emerges in adolescence when important changes occur in cognitive, emotional, and social processes. Mentalizing, alexithymia, and impulsiveness represent key dimensions for the understanding and interpretation of psychological difficulties in AN. The outbreak of the COVID-19 pandemic has impacted adolescents with AN, showing a worsening of the disease. The main aims of the present paper are (1) to compare adolescents with AN before and during the COVID-19 pandemic and (2) to explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…It appears that psychological functioning was more characterized by behavioral and bodily aspects than mental functioning [33]. Looking at the effects of the COVID-19 pandemic, similar studies have also reported an association between body-related symptoms and the pandemic [14], as well as a higher prevalence of binge-eating episodes [20] and a perceived "loss of control" [34]. From this perspective, the COVID-19 pandemic may have had a significant impact on the clinical presentation of AN as a result of sudden confinements, disruption of daily routines, and changes in interpersonal relationships and family dynamics [35,36].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It appears that psychological functioning was more characterized by behavioral and bodily aspects than mental functioning [33]. Looking at the effects of the COVID-19 pandemic, similar studies have also reported an association between body-related symptoms and the pandemic [14], as well as a higher prevalence of binge-eating episodes [20] and a perceived "loss of control" [34]. From this perspective, the COVID-19 pandemic may have had a significant impact on the clinical presentation of AN as a result of sudden confinements, disruption of daily routines, and changes in interpersonal relationships and family dynamics [35,36].…”
Section: Discussionmentioning
confidence: 91%
“…Looking specifically at AN, there is a growing body of evidence reporting a striking increase in the occurrence of new cases among young individuals during the pandemic, coinciding with the timing of social restrictions [19]. Several authors have already documented a change in the psychological presentation of AN during the pandemic [15,20], highlighting specific psychological burdens marked by heightened somatization, increased interpersonal sensitivity, greater levels of depression, different functioning profiles (i.e., personality traits), and heightened body uneasiness. However, it is crucial to note that AN is also marked by significant physical symptoms, encompassing cardiovascular, ionic, and hormonal aspects [21].…”
Section: Introductionmentioning
confidence: 99%
“…Among teenagers, RED represents one of the most common chronic diseases, predominantly affecting adolescent girls and young women (American Psychiatric Association, 2022). The COVID‐19 pandemic has notably exacerbated these disorders, worsening clinical features across various eating disorders (Bizzi et al, 2023; Gilsbach et al, 2022).…”
Section: Introductionmentioning
confidence: 99%